Genome-wide association study and drought tolerance evaluation of a winter wheat association mapping panel - Awad, Wahid, author; Byrne, Patrick, advisor; Haley, Scott, committee member; Qian, Yaling, committee member; Comas, Louise, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: drought; QTL mapping; wheat; GWAS; canopy temperature; root